Witnessing Sexual Harassment and Associated Substance Use and Poor Mental Health Outcomes among Adolescent Girls in the US - Elizabeth Reed; Marissa Salazar; Alma I. Behar; Niloufar Agah; Alice L. Wong; Jay G. Silverman; Melanie L. A. Rusch; Anita Raj (MDPI AG, 2023)
Direct experiences of sexual harassment have been found to be associated with substance use and poor mental health among girls. Indirect experiences, such as witnessing the sexual harassment of others, may be indicative of a climate supportive of sexual harassment against girls and elicit similar adverse outcomes. The current study sought to assess reports of witnessing sexual harassment and associations with substance use and mental heath outcomes among adolescent girls. The data were from questionnaires among girls (n = 152) ages 15-19 recruited from a health clinic serving a low-resource community in San Diego County. Using crude and adjusted regression models, we assessed witnessing the sexual harassment of girls (past year) as well as the frequency of witnessing such acts in relation to substance use, anxiety, depression, and suicidal ideation. The adjusted models included demographics and direct experiences of sexual harassment (past 6 months) as covariates. The participants had an average age of 17, and 76% were Latina. The majority (70%) reported witnessing sexual harassment (past year); 65% reported directly experiencing sexual harassment (past 6 months). Among those reporting witnessing, most witnessed sexual harassment at school (69%), at a party (45%), in their neighborhood (34%), or on public transport (33%). In adjusted logistic regression models, witnessing sexual harassment was significantly associated with past 30-day alcohol use, ever using drugs, feeling depressed (past 30 days), feeling anxious (past 30 days), and past-year suicidal ideation (ORs range 2.9-18.2). The findings suggest that, in addition to direct experiences of sexual harassment, indirect experiences of witnessing the sexual harassment of others may also be associated with negative outcomes regarding girls' health and well-being.